The development of cello technique in the string quartets of Joseph Haydn with special reference to (a) the various external influences causing this development and (b) the potential use of the cello parts within a teaching situation - Sholto-Douglas, Ishbel Elizabeth Fraser (Rhodes University, Faculty of Humanities, Department of Music, 1982)
From Introduction: In the middle of the eighteenth century, when Haydn began composing his first string quartets, violin writing was highly advanced and the violin an established solo instrument, its supremacy already firmly endorsed by the Italian Violin Schools of the seventeenth and early eighteenth centuries. The pace of development of the cello, however, was not comparable to that of the violin, despite the fact that the first cello known to us was made in 1572.
Keywords: Haydn, Joseph, 1732-1809 -- Quartets, strings; Cello -- Methods; Cello -- Instruction and study